2020
DOI: 10.2147/cmar.s263747
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predicting Recurrence in Endometrial Cancer Based on a Combination of Classical Parameters and Immunohistochemical Markers</p>

Abstract: The aim of this study was to establish a nomogram to predict the recurrence of endometrial cancer (EC) by immunohistochemical markers and clinicopathological parameters and to evaluate the discriminative power of this model. Methods: The data of 473 patients with stages I-III endometrial cancer who had received primary surgical treatment between October 2013 and May 2018 were randomly split into two sets: a training cohort and a validation cohort at a predefined ratio of 7:3. Univariate and multivariate Cox re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The reason for the inconsistency with our study may be that the study population was limited to ER/PR+ and HER2- breast cancer patients not receiving NAC, and p53 was simply classified as negative and positive. Additionally, in endometrial cancer, another hormone-dependent malignancy in women, ER and p53 were found to be independent predictors of recurrence in patients after surgery [ 37 ], which is in agreement with our study.…”
Section: Discussionsupporting
confidence: 92%
“…The reason for the inconsistency with our study may be that the study population was limited to ER/PR+ and HER2- breast cancer patients not receiving NAC, and p53 was simply classified as negative and positive. Additionally, in endometrial cancer, another hormone-dependent malignancy in women, ER and p53 were found to be independent predictors of recurrence in patients after surgery [ 37 ], which is in agreement with our study.…”
Section: Discussionsupporting
confidence: 92%
“…were initially judged by primary physicians and reviewed by superior physicians. 2 Pathological type I of EC was defined as G1 and G2 endometrioid adenocarcinoma, type II was defined as G3 endometrioid adenocarcinoma and non-endometrioid adenocarcinoma including serous carcinoma, clear cell carcinoma, and other histotypes. 21 Interpretation of immunohistochemical results refers to the following steps: 5 high-power fields were randomly observed in "hottest spot" area of tumor, and 100 tumor cells were assessed per field, tumor cells with strong nuclear immunostaining were defined as positive cells, then average percentages (range 0-100%) of positive cells of the five fields for each molecular maker (Ki67, ER, PR, and P53) were calculated.…”
Section: Pathology and Immunohistochemistrymentioning
confidence: 99%
“…25 Recurrence was confirmed by more than two gynecological oncologists through physical examination, biochemical indicators, imaging examination and pathological biopsy. 2 According to the recurrence site, recurrence was divided into local recurrence and distant metastasis. Local recurrence included vaginal stump recurrence and central pelvic region recurrence.…”
Section: Pathology and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Various predictive models have indicated the influence of molecular subtypes on prognostic relevance within HR-EC. [35,44,[55][56][57][58]. In one study, favorable prognosis was reported in POLE-mt and MSI tumors in HR patients with 5 year recurrence-free survival (RFS) of 93% and 95%, compared to 42% and 52% for the CNH and the CNL group, respectively (p < 0.001) [39].…”
Section: Prognostic Impact Within High-risk Ec (Hr-ec)mentioning
confidence: 99%